Primary choriocarcinoma of the vulva. Issue 3 (1st May 2001) - Weiss, S.; Amit, A.; Schwartz, M. R.; Kaplan, A. L.
Abstract : Primary extrauterine choriocarcinoma is very rare, found mostly in the genital tract (tube, cervix, ovary, vagina). Other sites such as lungs, gastrointestinal tract, heart, brain and submentum also have been reported. A 31-year-old woman presented with abnormal uterine bleeding 6 weeks after her last menstrual cycle. Her HCG titer level was 900 mIu/ml. She underwent dilation and curettage (D & C). Pathology failed to reveal any chorionic villi. Further evaluation was done, including a second D & C, laparoscopy, exploratory laparotomy, CT, MRI and ultrasound which all failed to define a source for the elevated HCG titer which subsequently rose to 95, 000 mIu/ml 130 days after her last menstrual cycle. At that time a vulvar mass was observed. Fine needle aspiration (FNA) was positive for choriocarcinoma. The patient was treated with one course of methotrexate 60 mg intramuscularly every other day for 5 days. Actinomycin-D 0.5 mg given intravenously daily for 5 days was added to courses 2–7. Radiotherapy (4000 rads) was applied concomitant with the chemotherapy. The remainder of the mass was subsequently excised. The patient has remained with no evidence of disease for 10 years. This is the first case report of primary vulvar choriocarcinoma.